Dinâmica ambiental dos fragmentos florestais de Cerrado da bacia hidrográfica do Rio das Pedras, Itaberaí, Goiás - Nunes, Nelton Nattan Amaral (2023)
Watersheds are ideal units for geoenvironmental studies and analytical uses aimed at measur ing the effects of human intervention on these systems. In this sense, geoprocessing methods have contributed to these studies, allowing integrated analyzes of the landscape that allow tak ing into account biotic, abiotic and anthropic aspects. Thus, t his master's thesis aimed to de velop a study of the temporal and spatial dynamics of land use in the Rio das Pedras water shed (BHRP), in Itaberaí (Goiás) and, based o n an integrated analysis of the landscape, to evaluate the environmental conditions of Cerrado fragment s. The research development pro cess started with the characterization of the BHRP in its ge oenvironmental aspects, the map ping and description of the l and use and cover for the years 1992, 2002, 2012 and 2022, the mapping of the cerrado fragments to which they were mapped 4 types of fragments by size in the basin area, which were classified as: small, medium, large and very large. A total of 237 fragment s were mapped and landscape metrics indicators were applied to these, and 80.06% of these present high anthropic pressure in their surroundings, indicating potential for extinc tion. From environmental indexes it is possible to evaluate the vegetational co nditions, the NDVI ranged from <= 0.33 to >0.66 with intervals of 0.33, being possible to identify three characteristics for the vegetation of the basin fragments, where smaller values or equal to 0.33 shows some kind of deficiency in the plant in relation to pho tosynthetic production and vege tative vigor, from 0.33 to 0.66 shows moderately healthy characteristics and values above 0.66 very healthy plants, up to To note that the majority of cerrado fragments existing in the basin have greater vegetative v igor, where it was observed that most of the cerrado fragments present in the basin fall into the group of very healthy plants, occupying 69.7% of the area of the fragments, it should be noted that this occurs in medium, large and very large fragments. The water stress conditions of the NDWI fragments were also evaluated, with values less than 0.07 and greater than 0.32 being categorized as high stress with a range of < 0.07 to 0.15, moderate stress of 0 .16 to 0.32 and vegetation that does not show water s tress > 0.3225. It is noticeable that most of the fragments present in the basin present moderate stress, almost the entire basin, which consolidated moderate stress, corresponding to 54.2% of the fragments. All the analysis carried out, corroborated with the discussion on the importance of verifying the percentage of areas still occupied by natural vegetation in the BHRP, since the lack of these compromises biodiversity, the stability of the physical environment and the processes of recharge and drainage o f the drainages, which is why it bec omes relevant when it is commit ted to the advancement of agricultural activities in this morphoclimatic and phytogeographical domain.